Strategi Komunikasi dan Personal Branding Pengguna Facebook Pro Dalam Membangun Makna Sosial (Studi Kasus Pada Akun @Lhia Silaen) - Nova Florentina Silaen; Iin Soraya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research aims to understand how communication strategies and personal branding implemented by the owner of the Facebook Professional Mode account (@Lhia Silaen) shape social meaning in the digital space. This study employs a qualitative approach with a case study design, focusing on an in-depth analysis of digital communication practices, self-representation styles, and symbolic interactions between the account owner and the audience. Data collection techniques were conducted through in-depth interviews, digital observations, and content documentation, and analyzed using an interpretative approach. The results show that the communication strategy applied by the account owner refers to the principles of the Cocreational Model of Strategic Communication (Botan, 2017), where the communication process is carried out in a two-way, participatory, and collaborative manner with the audience. Meanwhile, personal branding is built through four main factors according to Montoya (2002), namely authenticity, consistency, credibility, and differentiation. The research findings indicate that the combination of communication strategies and personal branding produces social meaning that reflects values of professionalism, empathy, and digital credibility. The interaction between the account owner and the audience serves as a medium for forming a professional identity that is not only representative but also collaborative and emotional. Thus, this research strengthens the view that social media, particularly Facebook Pro, functions as a symbolic space where individuals negotiate identity and build social legitimacy in the digital era.